2022
DOI: 10.1002/casp.2634
|View full text |Cite
|
Sign up to set email alerts
|

Opposition to immigration: How people who identify with far‐right discourses legitimize the social exclusion of immigrants

Abstract: This study sought to develop our understanding of how people legitimize opposition to immigration. Thirty-eight interviews were conducted with people who self-identified with far-right anti-immigration discourses, in Italy (N = 23) and Portugal (N = 15). Using reflexive thematic analysis, we developed four related themes. In the first theme, 'They're guests': Legitimizing exclusion by differentiating (non-) immi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Biological and cultural differences are emphasised in Ventura's discourse, representing Black people as a threat to the “good Portuguese”. This representation has been used to legitimise opposition to those who do not look like white, catholic Europeans in Southern European countries (Fernandes‐Jesus et al, 2022). Thus, the historical representation of Portuguese society as living in multicultural harmony (see Valentim & Heleno, 2018) is problematised and stops being taken for granted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological and cultural differences are emphasised in Ventura's discourse, representing Black people as a threat to the “good Portuguese”. This representation has been used to legitimise opposition to those who do not look like white, catholic Europeans in Southern European countries (Fernandes‐Jesus et al, 2022). Thus, the historical representation of Portuguese society as living in multicultural harmony (see Valentim & Heleno, 2018) is problematised and stops being taken for granted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of immigrants in Portugal increased between 2015 and 2019 (Reis et al, 2020), immigration is often not considered a main concern in the country (Eurobarometer, 2020). However, previous research focusing on how supporters of far-right parties oppose immigration identified that representations of immigrants as "guests" who threaten the country's traditions and receive more benefits than those defined as natives were marginally reproduced in Portugal (Fernandes-Jesus et al, 2022). Once in Parliament, Ventura brought such representations into the public sphere, something that had been unusual in Portugal's democratic history.…”
Section: The Rise Of Chega and The Far-right Ideologymentioning
confidence: 99%